Carbon Sequestration Rates Using the Allometric Equations of the Fast Growing Paulownia tomentosa (Thunb.) in Central Nepal - Joshi, Nabin Raj; Pant, Gunanand (NPRC Journal of Multidisciplinary Research, 2026)
Background: Paulownia tomentosa (Thunb.), a fast-growing tree native to East Asia, has recently been introduced to plantations and agroforestry systems in Nepal for its carbon sequestration and land restoration potential. This study assessed the biomass, carbon stock and carbon sequestration rate of different-aged P. tomentosa trees and their parts and developed species-specific allometric equations for future use.Methods: Using destructive sampling of nineteen 15–20-year-old trees and their seven different traits (Pole, Branch, Leaf, Twig, Tap root, Lateral root and Fine root) in Nepal's mid-hills region, we developed allometric models based on diameter at breast height (DBH).Model selections were based on Akaike Information Criterion, RSE, adjusted R2 and Leave-One-Out Cross Validation (LOOCV).Results: The models calculated a mean baseline carbon stock of 149.81 tC ha⁻¹ in 2014, which increased to 202.01 tC ha⁻¹ by 2022, yielding a sequestration rate of 5.87 tC ha⁻¹ yr⁻¹. Based on the results of AIC, RSE, Adjusted R2 and LOOCV, the most optimal model is . DBH was a reliable predictor for biomass, while adding tree height did not improve model performance.Conclusion: These equations provide stakeholders with a tool to accurately estimate plantation productivity, supporting the adoption of P. tomentosa for environmental restoration and smallholder livelihoods in Nepal's central Himalayan region and similar climatic zones.